Atributos funcionais não estão correlacionados com sincronia em uma comunidade fitoplanctônica - Silva, Matheus Nunes da (2020)
Species abundance in a local community can be correlated over time. Similarly, the abundance of different local populations of a given species can vary synchronously. The study of these patterns, known as interspecific synchrony and population synchrony, respectively, may indicate the relative importance of interspecific interactions, environmental filters (at different spatial scales) and dispersal processes on the temporal dynamics of populations and communities. In addition, studies have sought to test whether the levels of synchrony (interspecific and population) are related to functional traits. For example, functionally similar species should have correlated dynamics under the effect of a strong environmental filter. As another example, a specialist species should have higher levels of population synchrony than a generalist species. Thus, in the first chapter of this dissertation, we used data on phytoplankton functional traits to test whether the level of interspecific synchrony between pairs of species is dependent on the functional dissimilarity between them. In addition, we tested whether the increase in functional diversity would influence community synchrony, which in turn, could affect community stability. In the second chapter, we tested whether specialist taxa would have greater spatial synchrony than generalists. For both chapters, we used a dataset on phytoplankton community in the Cana Brava Reservoir (Goiás State, Brazil). Our hypotheses were not supported by the results. However, in the first chapter, we found a predominance of positive correlations between species abundances, a result that indicates the importance of environmental filters. In the second chapter, the low values of population synchrony suggest that regional environmental factors were not strong enough to control population dynamics. In general, we suggest that future studies should test a similar set of traits to test the generality of correlates of synchrony.